Visual Effects: A Fake Indigenous Warrior, A Contested Hill and Urban Imaginaries of Indigeneity in Santiago de Chile. - Casagrande, Olivia; Barton, Jonathan R. (Bulletin of Latin American Research, 2023)
In Latin American cities, indigenous peoples' presence is often overlooked: symbols and iconographies either exclude them as a minority or 'memorialise' them as part of a distant past. Through ethnographic observation, walking and visual narrative analysis, and adapting Charles Hale's constructions of indigeneity, this article examines the different representations of indigeneity in urban public space in Santiago de Chile. It interrogates its forms and multiple meanings and the ways in which these are challenged and appropriated by current indigenous artistic production and activism, highlighting the struggle to emphasise contemporary, hybrid lived experiences rather than essentialised, neo‐colonial memorialisation. The article addresses urban imaginaries of indigeneity as an arena for the struggle between different representations, which are highly relevant to the new Chilean Constitution and demands for pluri‐nationalism, and form part of an ongoing (de)construction of entrenched power relations.